Pembangunan Rest API untuk Pengelolaan Rute Robot AGV di PT XYZ - Ramadhan, Fazri Egi; Haromain, Imam; Rosyidi, Lukman (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
The transportation process for automotive components at PT XYZ is still carried out manually, involving human labor, which has led PT XYZ to consider using Automated Guided Vehicle (AGV) technology to improve the efficiency and effectiveness of transportation processes. Although the implementation of AGV technology at PT XYZ can provide benefits in terms of increased efficiency and productivity, there are limitations in the AGV system. The route change process must be done manually by reprogramming each AGV one by one, which is time-consuming, labor-intensive, and increases the risk of errors and inconsistencies. This study aims to address these limitations by designing and developing a REST API to support the functionality of the AGV route management system. The method used is black box testing to evaluate the system's functionality without examining the internal code structure. The test results show that the system successfully meets user needs with a success rate of 100% from 101 test scenarios. The developed REST API can integrate AGV route data and publish and update routes through an MQTT broker. This research is expected to provide an appropriate solution to help PT XYZ realize its full potential in utilizing AGV technology.